Dow Magnesium is Turning Seventy-Five. And the Revolutions Continue. - Dow Chemical Company (1991)
Print advertisement for the Dow Chemical Company's Magnesium Division highlighting the development of AE42X1, a new high-temperature magnesium alloy for use in automotive engineering.
Keywords: Magnesium alloys; Magnesium; Dow Chemical Company; Corporations; Advertising; Magnesium industry and trade; Chemical industry